Experiences of a decade of pharmacotherapeutic follow up to patients from a community at a public university - Delgado P, Gladys M (2012)
The pharmacotherapeutic follow up (PF) is a practice in which the pharmacist is responsible for the patients in relation to their drugs through pharmaceutical interventions to prevent, identify and solve drugs therapy problems (DTP). The aim of this study was to describe the experiences of a decade of PF in patients from the community at a public university. The study was descriptive and observational. The data were obtained from the notebooks, PF sheets and evaluation intervention sheets of Cabinet of Pharmaceutical Care of Faculty of Pharmacy and Biochemistry, San Marcos University; which were processed and evaluated in excel, with the following results: the attention to patients were made by residents of Clinical Pharmacy, from October 2003 to May 2012. 287 patients received pharmaceutical intervention: 163 women and 124 men, 90 patients with PF (35 attended less than a month, 29 a month to 1 year, and 26 over 1 year). The DTP found were 360 (279 reals: 181 DTP1, 9 DTP2, 11 DTP3, 30 DTP4, 11 DTP5, 37 DTP6) and the other 81 were potential DTPs). In these 360 DTP is observed: 114 pharmaceutical interventions that meet therapeutic goals (alternative dose (39 %), including medicine (39 %), alternative medicine (15 %), new therapeutic regimen (9 %), suspension of the prescription (7 %).